How advanced was Europe in 1760 after all? - Alam, M. Shahid (2000)
A review of the literature on historical comparisons of levels of development suggests that disparities between now and advanced and lagging countries around 1760 were most likely quite small and, if extreme observations at both ends are excluded, probably nonexistent. When purchasing power parity exchange rates are used for backward projections of per capita incomes, these disparities are nearly always smaller than two to one, and often much smaller than this. Comparison based on alternative indicators also suggest that disparities across countries were small or non-existent before 1800. - Reproduced
Keywords: Economic and social development - Europe; Europe - Economic history - 1760; Economic history